Метод пространственной оптимизации ступени осевой турбины с учетом обтекания турбинных профилей и периферийной протечки - Бойко, Анатолий Владимирович; Максюта, Дмитрий Игоревич (НТУ "ХПИ", 2014)
В работе приведен метод оптимизации ступеней осевой турбины с учетом обтекания турбинных профилей и периферийной протечки. Выполнены трехмерные расчеты исследуемой ступени. Проведено два этапа оптимизация по критерию повышения КПД. Расчетным путем повышен КПД изолированной ступени на 0,48 %. Получены интегральные и локальные по высоте характеристики потока. Сделан анализ полученных результатов. Представлены выводы относительно целесообразности применения данного метода при оптимизации турбин.

The development of the flow pass of powerful steam turbines contributes great lyto the efficiency of turbounits. This paper describes the method of the optimization of axial turbine stages taking into consideration the turbine profile flows and peripheral leakages. The verification of the numerical model and full-scale experiment have been described. Three-dimensional computations of the test stage have been done. Two steps of optimization in terms of the criterion of an increase in the efficiency factor have been realized. The first stage of optimization allowed us to reveal additional reserves for the improvement of the streamline. Using the computing method the efficiency factor of the isolated stage was increased by 0,48 %. Integral and local flow characteristics with regard to the blade height were obtained. The obtained results have been analyzed. The conclusions on the appropriateness of the use of this method during the turbine optimization have been made up.
A method of spatial optimization of axial turbine stage taking into account turbine profile flows and the peripheral leakage
Keywords: пространственное профилирование; разработка методики оптимизации; изолированная турбинная ступень; закон закрутки; spatial profiling; isolated turbine stage; twist law; peripheral leakage